Productivity in the Financial Services Sector - Jacob A. Bikker; Barbara Casu; Claudia Girardone; Mohamed E Chaffai; Michel Dietsch; Antonio Colangelo; Robert Inklaar; Marco Colagiovanni; Martin Czurda; Roger Hartmann; Charles-Henri Di Maria; Sandy Metzler; et al. (SUERF - The European Money and Finance Forum, 2009)
On 11-12 November 2008, SUERF and Banque Centrale du Luxembourg organized a conference on Productivity in the Financial Services Sector on the occasion of the tenth anniversary of the Banque Centrale du Luxembourg. The conference addressed three main themes: first, stylized facts on banks' productivity developments and the measurement of productivity; second, sources of productivity in banking; and third, the possible repercussions and consequences of the financial crisis on financial institutions' future productivity development. These three topics are taken up from various angles in the papers contained in the present volume, which represent a selection of the papers presented at the conference. Coming back to the three themes mentioned at the outset, the conference yielded some interesting results and raised many issues for further research. As regards theme 1, the papers presented overall suggest that financial integration in Europe has brought some, albeit according to some studies limited, convergence of bank efficiency among countries but on average productivity improvement has been weak. Various interesting attempts to capture banks' output were presented, but the various performance and efficiency measures yield different results. Linked to the difficulty of measuring the value of financial institutions' services, it remains far from clear what the "fair value" of a bank should be. This problem may also in part explain the very sharp ups and downs of bank stocks recently. Concerning theme 2, sources of productivity in financial services, several potentially important factors were mentioned: investments in ICT, investments in human resources, the quality of managers and remuneration policy, process effectiveness, mergers and acquisitions and economies of scale, privatizations, risk diversification versus regional and/or product specialisation, and risk-taking. Yet, no unambiguous picture emerged on which of these factors are most important. Regarding theme 3, the financial crisis may have far-reaching implications on our view of financial innovation and efficiency, on the way how to measure productivity appropriately as well as on the future development of financial institutions' productivity. First, the question arises whether the quest for productivity and profitability may under certain circumstances compromise the quality of banks' services (such as, e.g. the care invested into credit assessments and risk monitoring) and as a consequence put the stability of banks and the financial system at risk. As the recent crisis and its underlying causes suggest, there may at times be trade-offs between innovation and financial stability. If financial supervision and risk management do not keep up with financial innovation, the social value of such innovation may not be positive at all times. Financial innovation may also have blurred signals on banks? financial and risk positions, and thus have misled bank shareholders, clients and supervisors in their assessment of banks? business models and conduct of business. Second, the crisis might also affect banks? future performance: Increased government interference and stricter surveillance and capital adequacy rules might curb banks? profitability and efficiency, as measured by traditional performance indicators. However, the conventional measures of performance as presented and discussed at the conference - however varied and multifaceted they may be in trying to measure efficieny (i.e. the avoidance of unnecessary costs in the production process) and competition (the avoidance of inappropriately high profits) - basically seem to have a short-term focus. A longer-term perspective would also consider e.g. the financial institutions? solvency and the safety of deposits, as well as their stability and continued performance in periods of severe stress. Such extensions to the concept of ?performance? should certainly be explored more deeply in the light of the current crisis. In particular, bank efficiency should be considered by supervisors with a view to its influence on risk behaviour. The current debate on regulatory reform in response to the crisis also addresses the need for closer international coordination among supervisory regimes. Tighter regulatory coordination may, on the one hand, close regulatory loopholes, thus curbing banks? profit opportunities, at least in the short run. On the other hand, international harmonization of regulatory rules may generate considerable cost savings for internationally active financial institutions. By contributing to financial market integration it could also stiffen competition and in this way improve efficiency. A related issue is how the crisis will affect the size of banks in the future. Will consolidation in the sector ultimately result in fewer and bigger banks? Or will governments? and regulators? bad experience with institutions which are ?too big to fail? create pressure towards more and smaller institutions? The outcome of this may in turn have possible implications for competition and thus, ultimately, on future innovation, efficiency and productivity developments. Finally, in the coming months and years the issue of exit strategies from state intervention will have to be solved. In particular, how long should partial or full nationalisations of troubled banks last? Historical experiences vary, ranging from rather rapid re-privatisations in some cases to continued strong government influence decades. How can banks? increased reliance on government assistance be abolished and market-based incentives for productivity-enhancing strategies be restored, given the massive moral hazard created by the ? unavoidable ? government bail outs of banks? In conclusion, the conference demonstrated that various disciplines ? business administration, management, organisation and economics ? as well as different professional perspectives ? those of academia, practitioners and of policy makers ? need to be combined to do full justice to the complexity of the subject at hand. SUERF?s triple constituency and multiple-discipline approach again proved particularly suitable to approaching such a far-reaching topic.
Keywords: 330; Finanzsektor; Produktivität; Technische Effizienz; Finanzmarktregulierung; EU-Staaten; Welt